The Resilience of Families with Cerebral Palsy Children: Implications for Social Protection - Dwi Amalia Chandra Sekar; Isbandi Rukminto Adi; Rizky Putri Rachmawati (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2021)
There are generally agreed by both professional workers and laymen that the resilience of families is influenced by emotional climate of the family. This study aims to provide an overview of resilience in families with children who have cerebral palsy, who attend YPAC (Foundation for Disabled Children), which is the only centre for cerebral palsy services in Jakarta. Qualitative research was used to analyse a case study featuring three (3) separate families, with each family having two (2) children with cerebral palsy. The result of this study describes the Family Resilience by looking at risk factors and protective factors in families with Cerebral Palsy children and all their limitations. Risk factor is the condition of the informant, who has insufficient and unstable income. On the other hand, family members also receive discrimination regularly, and even experienced physical violence. Meanwhile, protective factor is a source of strength from their personality or values of each member of the family, commitment, and support from the surrounding environments, such as extended family, friendship groups, neighbours, and institutions. Social support becomes a source of strength for the family and keeps their fight with their children with cerebral palsy. Apart from internal factors, their relation to their environment also supports the family’s resilience.